2007
DOI: 10.1149/1.2719609
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Distribution of Carbon Nanotubes in Solution-Processed Polyaniline/Carbon Nanotube Composites

Abstract: Composites of high-molecular-weight polyaniline ͑PANI͒ and single-walled carbon nanotubes as well as composites of PANI and multiwalled carbon nanotubes of various weight percentages were prepared using solution processing. The integration and distribution of the carbon nanotubes ͑CNTs͒ in the PANI matrix were investigated by various characterization methods. CNT distribution was evaluated using scanning electron microscopy, while CNT dispersion and alignment were characterized by transmission electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…This is in accordance with the fact that as the MWCNT concentration increases, the conductivity of the composite increases. This procedure in the I-V characteristics is in agreement with the results reported by other investigators regarding in situ polymerized and solution processed composites [17,18].…”
Section: Resultssupporting
confidence: 92%
“…This is in accordance with the fact that as the MWCNT concentration increases, the conductivity of the composite increases. This procedure in the I-V characteristics is in agreement with the results reported by other investigators regarding in situ polymerized and solution processed composites [17,18].…”
Section: Resultssupporting
confidence: 92%
“…Suitable matrices include the transparent and widely available poly(methyl methacrylate) and polystyrene. Polyaniline represents another possible matrix; in that case, percolation requires only a close approach of nanotubes, rather than direct contact, and even lower loading levels are possible (20,21). A polyaniline-nanotube composite with loading levels on the order of 1% was patterned by use of laser ablation-induced dry transfer to make conductive lines suitable for organic electronics (22).…”
Section: Figurementioning
confidence: 99%
“…According to the SEM images, it is found that the work electrode is completely covered by PANI/CNT composites after three cycles. The porous network structure of PANI/CNT films can offer more approaches for electron transport and facilitate ion transmission [14] .…”
Section: Morphologiesmentioning
confidence: 99%